2019
DOI: 10.1108/pijpsm-12-2017-0154
|View full text |Cite
|
Sign up to set email alerts
|

How commitment and satisfaction explain leave intention in police force?

Abstract: Purpose The purpose of this paper is to investigate the impact of professional commitment and job satisfaction on leave intention considering alternative job opportunities as a moderator. Design/methodology/approach The authors collected data from 147 patrolling police officers on the basis of convenience sampling using a questionnaire-based survey. Findings The study noted that professionally committed and satisfied police officers are less likely to leave their organization. In addition, alternative job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…OC often has a clear correlation with the actions and performance of employees. If an employee has an OC, there will be fewer chances for absence and turnover (R. Ahmad, Islam, & Saleem, 2019;Igbaria & Greenhaus, 1992;Joe-Akunne & Ezeh, 2019;Karunarathne & Wickramasekara, 2020). Therefore, it is crucial to regularly review employees' commitment to resolving any problems that may occur and ensure that workers maintain a good attitude to work, which is indispensable to overall organizational success.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…OC often has a clear correlation with the actions and performance of employees. If an employee has an OC, there will be fewer chances for absence and turnover (R. Ahmad, Islam, & Saleem, 2019;Igbaria & Greenhaus, 1992;Joe-Akunne & Ezeh, 2019;Karunarathne & Wickramasekara, 2020). Therefore, it is crucial to regularly review employees' commitment to resolving any problems that may occur and ensure that workers maintain a good attitude to work, which is indispensable to overall organizational success.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Second, the data of our study were collected at one point of time, which may restrict to develop causality (Aguinis and Glavas, 2012;Ahmad, Islam and Saleem, 2018). Therefore, for further research in this area, it is suggested to conduct longitudinal studies.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Moreover, Shim et al (2015) verified that general strain theory can be applied to a police profession, and negative emotions had significant mediating impacts on the relationship between strain and TI. Ahmad et al (2018) used organisational theory as a framework to affirm that satisfied and professionally committed and devoted police officers are unlikely to quit police organisations.…”
Section: Literature Reviewmentioning
confidence: 99%